1993
DOI: 10.1210/jcem.77.3.8370707
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin rhythm in human milk.

Abstract: The pineal hormone melatonin exhibits a circadian rhythm in body fluids. No data are available on melatonin in human milk. The present study was undertaken to determine whether melatonin is detectable in human milk and, if so, whether it exhibits a daily rhythm. Blood and milk were sampled between 1400-1700 h and again between 0200-0400 h from 10 mothers 3-4 days after delivery. Melatonin in both fluids was beyond the limit of detection during the day, whereas during the night, its concentration was 280 +/- 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1
5

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 6 publications
5
87
1
5
Order By: Relevance
“…The evolution of human breastfeeding has resulted in a circadian modulation of the contents of breast milk, including in the levels of breast milk melatonin (88). It is of note that many of the factors in breast milk can act to regulate melatonin, suggesting that the varying breast milk constituents may differentially modulate levels of gut melatonin, with relevance to bacterial swarming (38) as well as melatonin's maintenance of the gut barrier (39).…”
Section: Breastfeeding: Modulation Of the Gut And Gut-brain Axismentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of human breastfeeding has resulted in a circadian modulation of the contents of breast milk, including in the levels of breast milk melatonin (88). It is of note that many of the factors in breast milk can act to regulate melatonin, suggesting that the varying breast milk constituents may differentially modulate levels of gut melatonin, with relevance to bacterial swarming (38) as well as melatonin's maintenance of the gut barrier (39).…”
Section: Breastfeeding: Modulation Of the Gut And Gut-brain Axismentioning
confidence: 99%
“…The night-time rise in pineal melatonin increases circulating maternal melatonin levels, which are transferred in the breast milk to the sucking infant, along with NAS and various melatonin metabolites (88). Consequently, night-time breast milk has higher levels of melatonergic pathway products that may, among other effects, act to entrain the infant's developing circadian rhythms.…”
Section: Breastfeeding and Melatoninmentioning
confidence: 99%
“…Emerging data have suggested that the effects of maternal hormones are transmittable through breast milk. One of the first examples of milk-borne hormones was melatonin, which was suggested to guide the development of a sleep-wake cycle in infants (1).…”
Section: To the Editormentioning
confidence: 99%
“…69 Other aspects of routine care practices with temporally related activity and auditory stimulation, timing of feeds and even the timing of expressing of mother's breast milk 425 may also function as non-visual circadian cues.…”
Section: To 32 Weeks Gestational Age and Beyondmentioning
confidence: 99%